2021
DOI: 10.3389/fsurg.2021.729736
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of High Frequency Auditory Perception After Robot-Assisted or Manual Cochlear Implantation in Profoundly Deaf Adults Improves Speech Recognition

Abstract: Background and Purpose: Robot-assisted cochlear implantation has recently been implemented in clinical practice; however, its effect on hearing outcomes is unknown. The aim of this preliminary study was to evaluate hearing performance 1 year post-implantation whether the electrode array was inserted manually or assisted by a robot.Methods: Forty-two profoundly deaf adults were implanted either manually (n = 21) or assisted by a robot (RobOtol®, Collin, Bagneux, France) with three different electrode array type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Robotic systems, such as HEARO®, Rosa®, which drill a narrow tunnel (direct cochlear access) from the cortex to the cochlea, need an alternate solution for stabilizing the electrode. EM has not been reported in the limited series of patients operated on who have had robotic insertions ( 12 15 , 17 , 18 ). Although the narrow tunnel approach itself provides some stabilization and the absence of coiled excess electrode lead in the mastoid cavity minimizes the EMs, caution is needed in fixing the electrode in the tunnel, which might be accomplished, for example with bone paté.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Robotic systems, such as HEARO®, Rosa®, which drill a narrow tunnel (direct cochlear access) from the cortex to the cochlea, need an alternate solution for stabilizing the electrode. EM has not been reported in the limited series of patients operated on who have had robotic insertions ( 12 15 , 17 , 18 ). Although the narrow tunnel approach itself provides some stabilization and the absence of coiled excess electrode lead in the mastoid cavity minimizes the EMs, caution is needed in fixing the electrode in the tunnel, which might be accomplished, for example with bone paté.…”
Section: Discussionmentioning
confidence: 97%
“…Cadaveric temporal bone experiments show that, in particular, the occurrence of ESD is decreased in motorized co-axial insertion with a slow steady speed ( 102 ). Yet, even in the limited series of RACIS, ESD has been reported with pre-shaped electrodes ( 17 ). With straight electrodes, RACIS can better manage co-axial insertion into the ST, minimizing damage to the scalar walls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preserving residual hearing and developing a less traumatic insertion of the electrode array have been main goals for many institutions, which could potentially be achieved using robotic surgery [20][21][22]. There is limited knowledge on post-robotic insertion hearing outcomes, but recent studies have shown that the robot itself is able to decrease the involuntary movements such as tremor; creates a smooth insertion and the translocated electrodes were decreased in comparison to manual insertion with reduced intracochlear damage, however, navigation and preoperative planning are still under refinement.…”
Section: Potential Impact and Future Applicationsmentioning
confidence: 99%